Establishing American Literature Through James Fenimore Cooper's The Deerslayer - Agustina, Mia Fitria (English Education Department, Universitas Islam Indonesia, 2013)
Women have very unique characteristics. They are far different from men. Therefore, women needs are also different from men needs including the need to read. Men tend to read adventure works. The adventure works fulfill man's need to taste the adventure as the hero-individual or group in adventures works is able to overcome obstacles and dangers to accomplish some important and moral mission. In another hand, women prefer to read romance ones. It is because romance formula provides what women desired. Moreover romance works are the feminine equivalent of the adventure stories. Furthermore, chick-lits, the women best friend, is one of the romance works. As it is used romance formula, chick-lits has ability to provide women's desire. It transforms the need, and interprets it through the narrative of chick-lits. That is why, because to find out how the interpretation of the works is an fascinating challenge, this paper tries to see the connection between chick-lits romance formula and how it affects the readers, the women.Key words: chick-lits, women, romance formula, and the needs